The oldest fossil record of Philopotinae (Diptera: Acroceridae) from the mid-Cretaceous amber of Northern Myanmar - Feng, Qi; Zhuang, Jialiang; Shih, Chungkun; Ren, Dong; Wang, Yongjie (Zootaxa, 2024)
A new genus and species of Acroceridae Leach, 1815, Burmophilopota wintertoni gen. et sp. nov., is identified from mid-Cretaceous Burmese amber, representing the oldest member of Philopotinae Schiner 1868. Based on morphological comparisons, Burmophilopota wintertoni gen. et sp. nov. most likely represents a stem group of the Philopotinae. The new material with well-preserved details of mouthparts and complete wing venation suggests that the new species could possibly be a pollinator for the angiosperms. This finding enhances our understanding of early origin and evolution of pollinating flies during the Mesozoic period.